PREVALENCE OF CRYPTOSPORIDIUM OOCYSTS IN THE WATER OF AL-DEHAB AL-ABYAD VILLAGE IN BAGHDAD- IRAO - Rahif, R. H.; Al-Gylani, B. A. W. (The Iraqi Journal of Veterinary Medicine, 2002)
Detection of oocysts of Cryptosporidium in water of Al-Dehab AL-Abyad village was carried, from January to December 2001, through examination of 240 different water samples, using millipore cartridge filter and an alternative Iraqi filters. The oocysts were revealed in 73 samples in rate of 30.41%, all water samples collected from ponds revealed oocysts, in 29.16 % of water tanks and 22.91% of sewage samples. Oocysts were not found in the water samples from municipal water supply. Statistical differences (P<0.05) in the presence of oocysts in the different samples were revealed. The alternative tissue filter was efficient for isolation of oocysts in comparison with the imported filters. Differences were found in the measurement and shape of isolated Cryptosporidium oocysts, and they were ranged from round (4.3 * 3.9 - 5 x 4.2 Mm) to oval (7.4 *5.5-8 x 6 mm) and they were also varied in the number according to the samples.